Case report: Blepharospasm in peak-dose dyskinesia may benefit from amantadine in Parkinson's disease - Fan, Qian-Ya; Zhang, Xiao-Dong; Hu, Ze-Di; Huang, Shi-Shi; Zhu, Shi-Guo; Chen, Cai-Ping; Zhang, Xiong; Wang, Jian-Yong (Frontiers in Neurology, 2022)
Introduction Blepharospasm is uncommon in Parkinson's disease, especially in the peak-dose dyskinesia period. Case presentation We herein present the case of a patient with PD who developed blepharospasm in the peak-dose dyskinesia period. The symptom was improved by taking amantadine. Conclusion The current report expands the phenomenology of peak-dose dykinesia in PD to include dystonic blepharospasm. This complication of levodopa therapy may respond to amantadine despite the dystonic appearance of movements.